2011
DOI: 10.1002/lsm.21046
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic suppression of Enterococcus faecalis using the photosensitizer mTHPC

Abstract: The results show that aPDT using the PS mTHPC incorporated in liposomes could be a new approach to adjuvant treatment of endodontic infections with E. faecalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 64 publications
(75 reference statements)
1
36
0
12
Order By: Relevance
“…In vitro, ex vivo, and in vivo studies using aPDT have shown that this approach has the potential to maximize root canal disinfection (18)(19)(20)(28)(29)(30)(31)(32). However, to the best of the authors' knowledge, there is so far no study evaluating the response of apical and periapical tissues to the use of aPDT in the endodontic treatment of teeth with apical periodontitis (ie, with the presence of tissue infection at the beginning of the treatment).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, ex vivo, and in vivo studies using aPDT have shown that this approach has the potential to maximize root canal disinfection (18)(19)(20)(28)(29)(30)(31)(32). However, to the best of the authors' knowledge, there is so far no study evaluating the response of apical and periapical tissues to the use of aPDT in the endodontic treatment of teeth with apical periodontitis (ie, with the presence of tissue infection at the beginning of the treatment).…”
Section: Discussionmentioning
confidence: 99%
“…34 Tests with liposomal mTHPC formulation demonstrated the complete inactivation of E. faecalis after a total energy dose of 100 J cm −2 , but at a higher concentration of PS (50 μM). 28 The natural chlorin Ce 6 and its conjugates with poly-L-lysine ( pL) or polyethyleneimine are among the chlorin derivatives with high antimicrobial activity. An ultra-pure Ce 6 at the concentration of 20 μM showed strong inactivation of P. aeruginosa and E. coli, using a red laser diode (λ = 664 nm, 588 mW cm −2 ) as a light source.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of new applications, a study investigated the antimicrobial effect of liposome enriched mTHPC for the use of Foscan in periodontal diseases. Enterococcus faecalis could be photoinactivated with 50 M mTHPC and 100 J.cm -2 indicating the possibility of adjuvant treatment of endodontic infections [21]. Related investigations include studies on the mechanism of cell death [22], the suppression of dark toxicity in PLGA nanoparticles [23], invasosomes for skin delivery of temoporfin [24], amongst others.…”
Section: Simple Modifications and Formulations Of Mthpcmentioning
confidence: 99%